Large amplitude oscillations for a class of symmetric polynomial differential systems in R³ - Llibre, Jaume; Messias, Marcelo [UNESP] (Academia Brasileira de Ciências, 2007)
Neste trabalho estudamos uma classe de campos vetoriais polinomiais com simetria, definidos no R³ e dependendo de um parâmetro real épsilon, que possui um conjunto de retas invariantes paralelas que tendem para dois pontos singulares no infinito, formando ciclos heteroclínicos degenerados. A análise global na vizinhança dos pontos no infinito é desenvolvida utilizando-se a compactificação de Poincaré. Provamos que para todo n Î N existe épsilonn > 0 tal que, para todo 0 < épsilon < épsilonn, o sistema considerado possui pelo menos n órbitas periódicas de grande amplitude, que bifurcam do ciclo heteroclínico formado pelas duas retas invariantes mais próximas do eixo-x, uma contida no semi-espaço y > 0 e a outra contida no semi-espaço y < 0.

In this paper we study a class of symmetric polynomial differential systems in R³, which has a set of parallel invariant straight lines, forming degenerate heteroclinic cycles, which have their two singular endpoints at infinity. The global study near infinity is performed using the Poincaré compactification. We prove that for all n Î N there is epsilonn > 0 such that for 0 < epsilon < epsilonn the system has at least n large amplitude periodic orbits bifurcating from the heteroclinic loop formed by the two invariant straight lines closest to the x-axis, one contained in the half-space y > 0 and the other in y < 0.
Keywords: ciclo heteroclínico infinito; órbitas periódicas; sistemas reversíveis; infinite heteroclinic loops; periodic orbits; symmetric systems